The Relations of Defense Budget with Investment: Evidence from Indonesia - Kennedy, Posma Sariguna Johnson (International Journal of Economics and Financial Issues, 2016)
There are two fundamental elements in building the strength of a country, the economy and defense. Both of these variables influence each other. A country with good economy will be able to provide sufficient defense budget. Meanwhile, good defense can provide indirect effect on the economy. The indirect impact of defense budget to economic growth is through investment. The study was conducted to examine whether the defense budget effected on the economy, particularly investment. Single equation set up to capture the effect of the defense budget on investment individually. The empirical results indicate that, the effect of the increase in the defense budget and the change in non-defense, led to the crowding out effect on investment. Keywords: Investment; Defense Budget; Defense Economics JEL Classifications: E65; E22; F52